International business and the development of innovation through business culture (LACCEI, 2024)
Innovation and cultural differences are two topics frequently study for international business. However, the link between the three concepts has been unusual. Does culture affect the way international trade stimulates innovation? This descriptive study, based on a compilation of research published between 1980 and 2020, seeks to theoretically describe the relationship between international business and the development of innovation through national culture. As a pragmatic link, the Hofstede dimensions and the Doing Business and Global Innovation Index are presented. The results indicate that international business provides strong incentives for the development of innovation. Likewise, current academic trends identify four combinations of cultural archetypes that energize the ecosystem of international business and innovation. Thus, the study concludes that culture has a double impact on the relationship between international business and innovation. On the one hand, there are cultural archetypes that promote the advancement of foreign trade and that simultaneously stimulate the capacity for innovation. On the other hand, such archetypes can determine the degree to which the incentives provided by international trade are absorbed and produce innovation.